Detection of Mutations of Antimutator Gene pfpI in Pseudomonas aeruginosa Species Isolated from Burn Patients in Tehran, Iran - Maryam Khalili-Samani; Mahmood Barati; Navid Mirmohammadsadegh; Mohsen Amin; Ali Samadikuchaksaraei (Pasteur Institute of Iran, 2019)
Introduction: Pseudomonas aeruginosa is an opportunistic pathogen of clinical importance, particularly in immunocompromised and burn patients. This bacterium is becoming resistant to many antibiotics via intrinsic or acquired mechanisms. Mutations in anti-mutator genes, such as pfpI, can be a potential intrinsic mechanism of antibiotic resistance. This study aimed to evaluate the possible effects of mutations of this gene on coding proteins of multi-drug resistant P. aeruginosa isolates. Methods: The antibiotic resistance pattern of 50 P. aeruginosa isolates against 9 anti-pseudomonas antibiotics was determined by the disk diffusion method. PCR, followed by sequencing, detected the mutations in the pfpI gene. The retrieved sequences were translated to the corresponding amino acid sequences using an online protein database. The amino acid sequences in mutated isolates were compared with the reference sequence using a multiple alignment method. Results: Out of 50 isolates, 43 (86%) were resistant to all antibiotics. Sequencing and multiple alignment analyses showed that amino acids in positions 21, 24, and 57 of pfpI gene were changed in resistant isolates, and all these mutations were observed in each isolate. Homology modeling showed that these amino acids were part of a cleft on the protease. The other point mutations resulted in amino acid changes were in positions 67, 83, and 165. Conclusion: The data obtained in this study showed that the pfpI gene of P. aeruginosa might have a significant effect on response to antibiotics. Further epidemiologic and comprehensive studies are required to confirm these findings.